Phytosterol supplementation enhances the growth performance, feed utilization, antioxidant status and glucose metabolism of juvenile largemouth bass (Micropterus salmoides) fed a high-starch diet - Liang, Qianrong; Huang, Yuanfei; Zhu, Ningyu; Bei, Yijiang; Shi, Wenrui; Chen, Xiaoming; Yao, Gaohua; Meng, Qinghui; He, Runzhen; Ding, Xueyan; Zhou, Fan (Frontiers in Marine Science, 2024)
To investigate the effects of dietary phytosterol supplementation on juvenile largemouth bass (Micropterus salmoides) fed a high-starch diet, a 56-day feeding trial was conducted with four dietary feeds for juvenile largemouth bass: extruded floating feed isonitrogenous and isoenergetic diets were formulated to contain 10% and 15% α-starch; on the basis of a 15% α-starch diet, two other diets were formulated with supplementation of 0.1% and 0.5% phytosterol, respectively. After the feeding trials, the survival rate, weight gain and specific growth rate, feed conversion ratio, intraperitoneal fat ratio, feed intake, protein efficiency ratio and activities of three digestive enzymes, as well as the concentrations of nine plasma biochemical indices, hepatic enzyme activities and glycogen contents, were measured and calculated, and the data were statistically analyzed. The results of the present study showed that the survival rate, weight gain and specific growth rates were significantly greater in plants fed high-starch diets supplemented with phytosterols. As the supplemental phytosterol concentration increased, the feed conversion ratio and intraperitoneal fat ratio significantly decreased; the protease and lipase levels in the pyloric zone markedly increased; the plasma cholesterol, triglyceride, glucose, malondialdehyde, aspartate transaminase and alanine transaminase levels significantly decreased; the glucokinase and pyruvate kinase levels markedly increased; and the hepatic glycogen content significantly decreased. In summary, dietary phytosterol supplementation promoted the growth performance, feed utilization and antioxidant status of juvenile largemouth bass fed a high-starch diet; enhanced glucose utilization and metabolism; and alleviated the negative stimulation of glycemia stress in M. salmoide fed a high-starch diet.